Pengaruh Larangan Ekspor Karang Hias terhadap Kondisi Terumbu Karang di Indonesia - Cahyo, Fitrian Dwi; Yudhistira, Muhammad Halley (UI Scholars Hub, 2024)
Indonesia has the largest coral population in the world, contributed as the world’s second largest ornamental corals exporter after Japan. Coral trade sparked the issues of habitat destruction, illegal trade, and coral health problems has prompted the government to banning of ornamental coral export. This study aims to find an empirical evidence does the policies mentioned above affect the condition of coral reefs in Indonesia. The author uses the Fixed-Effect Model on the Difference in Difference regression equation whose result show that export banning of ornamental corals does not significantly affect the condition of coral reefs in Indonesia.